(untitled) (The Planet, 2024)
Background: Spinal cord injury (SCI) poses significant challenges, impacting both physical and mental health. Early surgical decompression is proposed to enhance functional recovery and quality of life, but optimal timing and outcomes remain debated. This study investigates the effects of surgical decompression timing on neurological and functional recovery in SCI patients. Methods & Materials: This prospective cohort study involved 50 SCI patients (18–65 years) who underwent surgical decompression within 24 hours of injury. Baseline and follow-up assessments (1, 3, 6, 12 months) included ASIA, SCIM, MRI, VAS, SF-36, and complications. Data were analyzed using SPSS v26. Results: The mean age of participants was 35 years (SD ± 12), with 60% males. Decompression timing was <6 hours in 24%, 6-12 hours in 40%, and 12-24 hours in 36%. Significant ASIA score improvements were observed, with 36% of ASIA A patients improving to ASIA B by 12 months. SCIM scores increased from 25 (SD ± 10) to 60 (SD ± 20), while pain levels decreased from 7 (SD ± 2) to 3 (SD ± 1). Quality of life scores (SF-36) improved markedly in both physical and mental health domains. Complications included surgical site infections (6%), DVT (4%), PE (2%), and neuropathic pain (20%). Conclusion: Early surgical decompression within 12 hours post-injury significantly improves neurological and functional outcomes, reducing pain and enhancing quality of life in SCI patients. These findings support the critical role of timely surgical intervention in SCI management.